2004
DOI: 10.3141/1878-01
|View full text |Cite
|
Sign up to set email alerts
|

Why People Cross Where They Do: The Role of Street Environment

Abstract: The role of the street environment in the way people cross roads in urban settings is modeled. Respondents were placed in real traffic conditions at the curbside of street blocks in the Tampa Bay, Florida, area for 3-min observations of the street environments. Without crossing the blocks, respondents stated their crossing preference at each of six blocks. The origin and destination of each crossing were hypothetically set and varied across the blocks. So were the options available: two options for crossing at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 10 publications
0
39
1
1
Order By: Relevance
“…In order to incorporate this parameter in the model, some functions of the nested logit model are used (Chu et al, 2003). In particular, the mid-block branch options of the nested logit model were not exploited so far, but were simply used to obtain the total marginal probability for mid-block.…”
Section: Model For a Pedestrian Tripmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to incorporate this parameter in the model, some functions of the nested logit model are used (Chu et al, 2003). In particular, the mid-block branch options of the nested logit model were not exploited so far, but were simply used to obtain the total marginal probability for mid-block.…”
Section: Model For a Pedestrian Tripmentioning
confidence: 99%
“…Level 2: If junction, which one? In order to model this decision process, we used a nested logit model formulated by Chu et al (2003). In that study, a crossing scenario was presented to survey participants, who were asked to state their crossing preferences.…”
Section: Model For a Single Road Linkmentioning
confidence: 99%
“…Exceções são o estudo de aceitação de brechas apresentando vídeos aos pedestres, de Schmidt e Färber (2009), e o desenvolvimento de modelos de escolha do local de travessia, não apresentados neste artigo, que utilizam entrevistas, como o de Chu et al (2004). Esse capítulo apresenta uma revisão dos processos de coleta de dados relatados na literatura, em que a extração de dados foi feita de forma automática, semiautomá-tica e manual.…”
Section: Processos De Coleta De Dadosunclassified
“…Many studies can be found about pedestrian accidents characteristics [12,19], pedestrian's and driver's behaviour at crossings [3,4,6,9,17] and evaluation of measures enhancing pedestrian crossings safety [7,13].…”
Section: Introductionmentioning
confidence: 99%